Comparison of the effectiveness of group therapy for enriching marital relationships and forgiveness on the desire to compensate women involved in emotional divorce in Isfahan - Moghimi, Homa; Sharifi, Tayebeh; Latifi, Zohreh; Ahmadi, Reza (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to compare the effectiveness of group therapy for enriching marital relationships and forgiveness on the desire to compensate women involved in emotional divorce in Isfahan. Methods: The method of the present study was quasi-experimental with pre-test, post-test design and follow-up with a control group. The statistical population of the study included all women with emotional divorce who referred to clinics under the support of Isfahan Welfare Organization in 2020-2021 to receive family counseling services. Using purposive sampling method, 60 women were selected as a sample and randomly divided into three groups of first experiment (n = 20), second experiment (n = 20) and control (n = 20). The experimental groups received Olson's (1999) marital relationship enrichment intervention in seven sessions and Enright's (2001) forgiveness intervention in nine sessions during two months. Gotman's emotional divorce questionnaire (1997) and Woodyat and Wenzel's (2013) willingness to compensate were used to collect data. The data were analyzed using variance analysis with repeated measurements. The data were analyzed using repeated measures analysis of variance. Results: The results showed that the intervention of marital relations enrichment is effective on the score of desire to compensate (F = 8.30, P = 0.001) and the intervention of forgiveness is effective on the score of desire to compensate (F = 6.15, P = 0.001) And this effect was stable in the follow-up phase. In connection with the comparison of the effectiveness of the intervention of marital relations enrichment and forgiveness, the results showed that the intervention of marital relations enrichment over time has more therapeutic stability compared to the teachings of forgiveness therapy. Conclusion: Based on the results of this study, the interventions performed in counseling centers and family psychological services, courts and welfare organizations can be used.